Geographies of Muslim women : gender, religion, and space - Falah, Ghazi-Walid; Nagel, Caroline Rose (The Guilford Press, 2005)
This volume explores how Islamic discourse and practice intersect with gender relations and broader political and economic processes to shape women's geographies in a variety of regional contexts.